Rethinking the Surveillant Assemblage in Palestine: Racialization, Friction, Speed - Ghantous, Wassim (Surveillance & Society, 2025)
This intervention rethinks Haggerty and Ericson’s (2000) concept of the surveillant assemblage by situating it within the settler colonial conditions of Palestine. Through this engagement, it suggests a critical reassessment and theoretical refinement of the surveillant assemblage concept. While Haggerty and Ericson’s formulation marked a significant shift in surveillance studies—emphasizing multiplicity, decentralization, and virtuality—it remains rooted in political formations within the Global North, overemphasizes technological capacities, and insufficiently attendant to complexities of politics and power relations. Through recounting a critical analytical narrative on the workings of the Israeli surveillant assemblage in Palestine, the intervention re-evaluates three key aspects of the concept. First, by foregrounding coloniality as a central analytic, it thinks anew the virtuality of bodies within broader virtual-actual processes of racialization of bodies as well as territories. Second, it unsettles technological fixity and moves beyond statist and corporate control by reinstituting civilianized actors and everyday colonial encounters. Third, it problematizes the underlying prediction of a smooth convergence and expansion of surveillance technologies through centering frictions, tensions, and competitions. Accordingly, the intervention offers a preliminary revisiting of the surveillant assemblage in a way that augments its analytical capacity while rendering it politically generative.